Línea 100 en los egresados de la Facultad de Trabajo Social de la Universidad Nacional del Centro del Perú - Manrique Canchari, Ana (2023)
The world unfolds in violent situations that gradually enter the social microphysics: institutions, educational and work communities and the family. This is how violence is observed at the level of a couple, parental filial, fraternal, between family members; it is expressed in physical, verbal, psychological, economic, sexual abuse. The qualitative study shows domestic violence and how the Peruvian state slows down this serious public health problem. In this regard, it designs the policy of informing as part of the culture of reporting. In this process, state entities, civil society, professionals, graduates of those academic areas articulated to the social, participate. It is formulated as a general objective: Identify the opinions of the graduates of the Faculty of Social Work of the “Universidad Nacional del Centro del Perú” on line 100. It is important to know the level of perception and knowledge of the graduates, the same who work in multidisciplinary teams such as the Women's Emergency Center, Commissioners, among others. The graduates known from Line 100 as a free service, support the referral to the Family Prosecutor's Office; raise the need to evaluate the capabilities and timely care of the specialists who serve Line 100.